2017
DOI: 10.1177/0003489416689470
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Applied Topically to the Nasal Mucosa Increases the Transmucosal Nitrous Oxide Exchange for the Middle Ear

Abstract: Objective Determine if the middle-ear trans-mucosal Nitrous oxide (N2O) exchange-rate is affected by nasal inflammation caused by topical application of histamine. Methods In a randomized, double-blind, crossover study, twenty adults were challenged intra-nasally with histamine (5 mg) and placebo on separate occasions. At each session, the subjects were fitted with a non-rebreathing mask and breathed room-air for 20 minutes, 50% N2O:50% O2 for 20 minutes and 100% O2 for 10 minutes. Throughout, heart-rate, bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“… 54 A recent randomized, double-blind study tested the effects of intranasal histamine and placebo stimulation on middle ear pressure balance and gas exchange performance, and found that histamine could cause inflammation of the local mucosa and the distal mucosa, including the ET mucosa, thereby affecting ET opening and causing ETD. 55 In addition, many studies have shown that the use of intra-aural antihistamines in sensitized rat models can reduce the accumulation of middle ear fluid, improve OME symptoms, and may be effective in treating ETD caused by allergies. 56 , 57 , 58 …”
Section: Application Of Anti-allergic Therapy In the Development Of Etdmentioning
confidence: 99%
“… 54 A recent randomized, double-blind study tested the effects of intranasal histamine and placebo stimulation on middle ear pressure balance and gas exchange performance, and found that histamine could cause inflammation of the local mucosa and the distal mucosa, including the ET mucosa, thereby affecting ET opening and causing ETD. 55 In addition, many studies have shown that the use of intra-aural antihistamines in sensitized rat models can reduce the accumulation of middle ear fluid, improve OME symptoms, and may be effective in treating ETD caused by allergies. 56 , 57 , 58 …”
Section: Application Of Anti-allergic Therapy In the Development Of Etdmentioning
confidence: 99%